Socialização escolar infantil mediante a interação: um tema a partir de três enfoques piagetianos - Petter, Francine Bohne Ritta (2024)
This dissertation develops as its central theme school socialization through interaction, discussing it from three Piagetian approaches. The general objective is to explore authors of this tradition in order to understand how they approach school socialization children and what is the scope of their approaches to promoting practices in this direction in current affairs. The problem of the study is formulated as follows: What is the meaning attributed to children's school socialization in the theoretical approaches of Jean Piaget, Ives de La Taille and Joseph Maria Puig and what is its reach today? In order to address this issue, the methodological resource of hermeneutics was sought, through bibliographical and webgraphics of the mentioned authors and some of their commentators. The research is structured in three chapters. The first deals with moral socialization in Piaget, through the concepts of cooperation, reciprocity, mutual respect and solidarity. The second discusses the moral socialization in a neo-Piagetian sense in La Taille and in volume 8 of the Parameters National Curricular Studies (PCNs), which deals with ethics. The third begins by presenting examples of practices based on neoliberal educational policies and which take on a heteronomizing at school, which is why they contrast with socialization processes such as interaction and cooperation in the Piagetian and neo-Piagetian sense. As a counterpoint to such practices, we resort to Joseph Maria Puig and his conception of school socialization through moral practices. Based on this author, we discuss what a moral practice is and how Moral socialization can be enhanced by different types of moral practices. It is concluded that Piaget's perspective and the neo-Piagetian approaches of La Taille, the PCNs and Puig play an important role in promoting children’s school socialization practices in current affairs. This role becomes even more important because such perspectives theoretical, as they defend a conception of interaction markedly focused on autonomy, make it possible to confront heteronomizing socializing practices of a neoliberal nature, such as such as Reading programs anchored on digital platforms, Gamification, Education Finance and Homeschooling.